Pengembangan Modul berbasis Socio-Scientific Issues untuk Meningkatkan Problem Solving Skill Siswa SMP - Sohifa Aprilia (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The low problem-solving skills of students in science education have become the main issue identified in this research. This is due to the use of monotonous, theoretical learning resources that do not provide enough practice space to develop students' problem-solving skills. The purpose of this research is to develop a module based on Socio-Scientific Issues (SSI) and to describe the validity, practicality, and effectiveness of the module in improving the problemsolving skills of junior high school students. This research uses the Research and Development (R&D) method with the ADDIE model, which consists of five stages: analyze, design, develop, implement, and evaluate. The subjects of the research are ninth-grade students of SMP Negeri 1 Kedungjajang. The data collection instruments include validation sheets, implementation observation, pretestposttest tests, and student response questionnaires. The research results show that the SSI module has a validity level of 82.55% (fairly valid category), a practicality value of 84.65% (practical category), and an effectiveness value based on N-gain of 0.73 (high category). Additionally, student responses to the use of the module received a percentage value of 88.88% with a very good category. The conclusion of this research is that the Socio-Scientific Issues-based module is proven to be valid, practical, and effective for use in science education to enhance students' problem-solving skills on environmental issues. This module also provides contextual learning experiences relevant to students' daily lives and supports active and independent learning.
FINALISASI oleh Arif 2026 Juli 15
Keywords: problem-solving skills; socio-scientific issues; environmental issues